A Service-Learning proposal for Architecture, Building and Urbanism Students: getting involved in Education Tours in Madrid - Gabriel Pinto; Victoria Alcázar; María M. Conde; Ángel Aguero; Marina P. Arrieta; Freddys R. Beltrán; Patricia García-Muñoz; Javiera A. Sepulveda (Advances in Building Education)
A Service-Learning methodology has been employed by professors and students at the Universidad Politécnica de Madrid to design and conduct two educational tours: "Spanish Enlightenment and the discovery of three chemical elements" and "The ‘altos del hipódromo’, a significant area during the 'Silver Age' of Spanish culture (1868-1936)". The objectives include: providing a holistic education integrating science with art, history, and architecture; nurturing skills such as data research, teamwork, oral presentation, and creativity; disseminating cultural content widely to the general people; and deepening the understanding of Madrid's architectural and cultural heritage. Tailored for diverse audiences including international participants, scientific conference attendees, and students from specific areas, these tours also involve students and faculty from architecture, building, and urban planning backgrounds. This article reflects on these experiences, evolving into discussion of topics such as Madrid's urban development, historical cartography, architectural styles (Neoclassical, Iron, Functionalism, Neo-Mudéjar…), the progression of historical buildings, the lives and works of prominent architects, and the intersection between architectural heritage and tourism.